Revolutionizing language learning: Unleashing the power of the engage model to supercharge writing skill in cognitively more and less active EFL learners - Nikbakht, Ahmadreza; Neysani, Masoud; Amirjalili, Forough (Frontiers in Education, 2024)
The ever-growing need for fluency in written English around the world, because of the role of English as the world 's international language, has given priority to finding more effective ways to its teaching. The present study aimed to investigate the effect of using the ENGAGE Model on writing performance of EFL learners through a mixed-method study. The participants of the study were 60 advanced level female EFL learners with the age range of 20 to 30 in one of the private language institutes in Isfahan, Iran. The participants were non-randomly selected from a large pool of advanced female students. The selected participants were assigned to the two groups of the ENGAGE Model (the experimental group) and TBLT (the control group), with 30 students in each.The participants were also specified in terms of their cognitive ability as cognitively more or less active based on their answers to a validated cognitive profile questionnaire. In the quantitative phase of the study, the participants went through the processes of pretesting, intervention, and posttesting and the data collected were fed into the SPSS software version 26. The results revealed that the ENGAGE Model had a statistically significant effect on the writing development of cognitively more and less active EFL learners. The qualitative findings of the study proved that the cognitively more active learners enjoyed the ENGAGE Model class more than the cognitively less active ones.Likewise, the cognitively more active learners could benefit from the class more than their counterparts in the cognitively less active camp and assessed themselves more positively in terms of L2 writing. The finding of the study suggested that EFL teachers and stakeholders should increase interaction and higher-order thinking, and make connections to learners' previous learning.